Pemberdayaan Ekonomi Anggota Unit Jasa Keuangan Syariah Melalui Produk Simpanan DAN Pembiayaan Di Unit Simpan Pinjam Dan Pembiayaan Syariah As-Sakinah Surabaya - M. Haris Hidayatulloh; Moh. Qudsi Fauzi (Universitas Airlangga, 2016)
Islamic finances cooperation/Islamic finances servise unit as one of micro organization that has a role in developing and evolving the economical potential of its members in particular way, and the society in general way, to increase the economical and social prosperity.The aim of this research is to find out the role of Islamic finances cooperation unit in empowering the economies of its member. This researce is using the qualitative approach by case study as a strategy. The data collection is achieved by interviewing the related objects directly.This research indicated that the members experienced the role of Islamic savings and loan and budgeting unit of As-Sakinah Surabaya helpfully by offering its finances products, namely the deposit and the budgeting with many models upon the members fancies and the most important part of the 460 products is, the contracts are based on the Islamic law.